Pragmatic in Religion: Reinterpretation of the Qur'anic Interpretation of How to Prevent the Destruction of Nature - Devi Suci Windariyah (Islamika Inside: Jurnal Keislaman dan Humaniora, 2025)
This is a study of speech act analysis as part of pragmatic studies contained in the interpretation of the Qur'an by Ibn Kathir. In the Qur'an, Surah Al-Rum, verse 41, contains a reference to the seeming corruption on earth. The purpose of this study is to analyse the speech acts of Ibn Kathir's interpretation of natural damage, the factors that cause natural damage on earth, and the implications of speech acts (pragmatic) in Qur'anic studies. The results showed that the illocution contained in the interpretation of Ibn Kathir is assertive and directive. From the classification of speech acts, it is found that the factors that can cause natural damage are human sin and the loss of one's belief in God's supernatural power. The Pragmatic Implications of Ibn Kathir's interpretation are: affirmation of logical pragmatics, rejection of dualism, context and variability, interaction and negotiation, and implications for Comparative Ethics.